Panel of autoantibodies against multiple tumor‐associated antigens for detecting gastric cancer. Issue 3 (March 2017) - Hoshino, Isamu; Nagata, Matsuo; Takiguchi, Nobuhiro; Nabeya, Yoshihiro; Ikeda, Atsushi; Yokoi, Sana; Kuwajima, Akiko; Tagawa, Masatoshi; Matsushita, Kazuyuki; Satoshi, Yajima; Hideaki, Shimada
Abstract : Gastric cancer is the second leading cause of cancer death in the world, and effective diagnosis is extremely important for good outcome. We assessed the diagnostic potential of an autoantibody panel that may provide a novel tool for the early detection of gastric cancer. We analyzed data from patients with gastric cancer and normal controls in test and validation cohorts. Autoantibody levels were measured against a panel of six tumor‐associated antigens (TAAs) by ELISA: p53, heat shock protein 70, HCC‐22‐5, peroxiredoxin VI, KM‐HN‐1, and p90 TAA. We assessed serum autoantibodies in 100 participants in the test cohort. The validation cohort comprised 248 participants. Autoantibodies to at least one of the six antigens showed a sensitivity/specificity of 49.0% (95% confidence interval [CI], 39.2–58.8%)/92.4% (95% CI, 87.2–97.6%), and 52.0% (95% CI, 42.2–61.8%)/90.5% (95% CI, 84.8–96.3%) in the test and validation cohorts, respectively. In the validation cohort, no significant differences were seen when patients were subdivided based on age, sex, depth of tumor invasion, lymph node metastasis, distant metastasis, peritoneal dissemination, or TNM stage. Patients who were positive for more than two antibodies in the panel tended to have a worse prognosis than those who were positive for one or no antibody. Measurement of autoantibody response to multiple TAAs in an optimized panel assay to discriminate patients with early stage gastric cancer from normal controls may aid in the early detection of gastric cancer. Abstract : Autoantibodies to at least one of the six antigens demonstrated a quite high sensitivity/specificity and the efficacy of the panel for detecting gastric cancer was not affected by any of the clinical features of the tumors. This means that our panel of six TAAs helps distinguish patients with early‐stage gastric cancer from healthy controls. Besides, patients who were positive for more than two antibodies in the panel tended to have a worse prognosis than those who were positive for one or no antibody.